Priming effect of the addition of maize to a Japanese volcanic ash soil and its temperature sensitivity: a short-term incubation study. Issue 5 (3rd September 2019) - Iimura, Yasuo; Tabara, Issei; Izumitsu, Kosuke; Fujitake, Nobuhide
ABSTRACT: The response of soil organic matter (SOM) to global warming is a crucial subject. However, the temperature sensitivity of SOM turnover remains largely uncertain. Changes in the mineralization of native SOM, i.e., priming effect (PE) may strongly affect the temperature sensitivity of SOM turnover in the presence of global warming. We investigated the direction and magnitude of the PE in a Japanese volcanic ash soil at different temperatures (15°C, 25°C, and 35°C) using a natural 13 C tracer (C4-plant, maize leaf) in a short-term (25 days) incubation study. In addition, we evaluated the temperature sensitivity expressed as Q 10 value with and without the addition of maize to the soil and their relations to PE. We found that positive PE occurred at each temperature condition and tended to increase with decreased temperature, and these PE results were consistent with the microbial biomass at the end of the incubation period. CO2 emission from control soil (without maize) increased with increasing temperature ( Q 10 = 2.6), but CO2 emission from the soil with added maize did not significantly change with increasing temperature ( Q 10 = 1.0). This was caused by the suppression of CO2 emission from the soil with increasing temperature ( Q 10 = 0.9). On the other hand, soil-originated CO2 emission clearly increased with increasing temperature ( Q 10 = 3.4) when Q 10 values were calculated on the assumption that the temperature and substrate supply increase at the same time (from 25°C). These results suggest that not only the temperature increase but also the labile carbon supply may be important for the temperature sensitivity of Japanese volcanic ash soil.